Crystallization of Character Values of Banyumas Society in Central Java, Indonesia, 1830-1930 - Sukardi, Tanto (TAWARIKH, 2016)
ABSTRACT: In fact, the existed character values of society are result of an ongoing process of values crystallization. As an impact of flow of intensive cultural interaction, character values have also been experiencing shifts for adjustment. Crystallization in forming new values is also processing and accumulating forming character values in society as symbol of identity in a social community. This research aimed to describe the form of Dutch colonial intervention in Banyumas, Central Java, Indonesia; and continuity process of character values crystallization in the area. This research used historical method by using five steps of main activities, i.e. âHeuristicâ, as a step to collect historical sources; Criticism, as an activity to criticize sources both internally and externally; Interpretation to provide elucidation on data and facts; and Historiography, the phase of history writing by analysis based on the law of cause and effect, including the explanations. It was the writing phase along with commentary followed by concept and social theory by using multi-dimensional approach. The findings of the research described about the Dutch colonial intervention in Banyumas covering the areas of governance bureaucracy; economics covering tax sector, monetary; and policy for independent labor. Colonial intervention, that is gradually, also affected the process of crystallization on character values that became the characteristic of Banyumas society until now, consisting of value of self-identity, social solidarity, leadership, religion, and work ethic.KEY WORDS: Banyumas society, Dutch colonial intervention, social shift, value crystallization, and people character.About the Author: Dr. Tanto Sukardi is a Senior Lecturer at the Department of History Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. For academic interests, the author can be contacted via e-mail at: tanto_sukardi@yahoo.comHow to cite this article? Sukardi, Tanto. (2016). âCrystallization of Character Values of Banyumas Society in Central Java, Indonesia, 1830-1930â in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.173-182. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (March 1, 2016); Revised (March 21, 2016); and Published (April 28, 2016).